Correlation between acoustic divergence and phylogenetic distance in soniferous European gobiids (Gobiidae; Gobius lineage) - Horvatić, Sven; Malavasi, Stefano; Vukić, Jasna; Šanda, Radek; Marčić, Zoran; Ćaleta, Marko; Lorenzoni, Massimo; Mustafić, Perica; Buj, Ivana; Onorato, Lucija; Ivić, Lucija; Cavraro, Francesco; et al. (PloS one, 2021)
In fish, species identity can be encoded by sounds, which have been thoroughly investigated in European gobiids (Gobiidae, Gobius lineage). Recent evolutionary studies suggest that deterministic and/or stochastic forces could generate acoustic differences among related animal species, though this has not been investigated in any teleost group to date. In the present comparative study, we analysed the sounds from nine soniferous gobiids and quantitatively assessed their acoustic variability. Our interspecific acoustic study, incorporating for the first time the representative acoustic signals from the majority of soniferous gobiids, suggested that their sounds are truly species-specific (92% of sounds correctly classified into exact species) and each taxon possesses a unique set of spectro-temporal variables. In addition, we reconstructed phylogenetic relationships from a concatenated molecular dataset consisting of multiple molecular markers to track the evolution of acoustic signals in soniferous gobiids. The results of this study indicated that the genus Padogobius is polyphyletic, since P. nigricans was nested within the Ponto-Caspian clade, while the congeneric P. bonelli turned out to be a sister taxon to the remaining investigated soniferous species. Lastly, by extracting the acoustic and genetic distance matrices, sound variability and genetic distance were correlated for the first time to assess whether sound evolution follows a similar phylogenetic pattern. The positive correlation between the sound variability and genetic distance obtained here emphasizes that certain acoustic features from representative sounds could carry the phylogenetic signal in soniferous gobiids. Our study was the first attempt to evaluate the mutual relationship between acoustic variation and genetic divergence in any teleost fish.
Keywords: Animals; akustika; druhová specificita; Fishes; Species Specificity; Sound; zvuk; ryby; Genetic Variation; Stochastic Processes; Phylogeny; Acoustics; Vocalization, Animal; Sequence Analysis, DNA; stochastické procesy; zvířata; sekvenční analýza DNA; fylogeneze; genetická variace; vokalizace zvířat